1994
DOI: 10.1111/j.1399-3054.1994.tb03013.x
|View full text |Cite
|
Sign up to set email alerts
|

A morphological and cytological study of Petunia hybrida exposed to UV‐B radiation

Abstract: The aim of this study was to investigate whether the cytoskeleton, and in particular the microtubular system, is affected by enhanced levels of ultraviolet‐B (280–320 nm, 9 kJ m−2 day−1 biologically effective UV‐B radiation) radiation in epidermal cells of Petunia x hybrida Vilm, isolated from leaves of plants grown under UV‐B radiation and visible light. In addition, morphological changes during development were monitored. In a previous study microtubules were depolymerized and delays in the different stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The hypothesis that UV‐B acts on cell division requires confirmation through more detailed microscopic analysis. However, it is notable that Dickson & Caldwell (1978) showed that UV‐B altered the rate of cell division in Rumex patientia , resulting in smaller leaves and slower early growth rates, while in Petunia hybrida , increased leaf area under elevated UV‐B was attributed to increased cell division (Staxén & Bornman 1994). As cell division ceases earlier in epidermal tissues than in the mesophyll, the number of epidermal cells is determined at an early stage of development of the leaf primordium (Korner & Pelaez Menendez‐Riedl 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that UV‐B acts on cell division requires confirmation through more detailed microscopic analysis. However, it is notable that Dickson & Caldwell (1978) showed that UV‐B altered the rate of cell division in Rumex patientia , resulting in smaller leaves and slower early growth rates, while in Petunia hybrida , increased leaf area under elevated UV‐B was attributed to increased cell division (Staxén & Bornman 1994). As cell division ceases earlier in epidermal tissues than in the mesophyll, the number of epidermal cells is determined at an early stage of development of the leaf primordium (Korner & Pelaez Menendez‐Riedl 1989).…”
Section: Discussionmentioning
confidence: 99%
“…(2005) to suggest that a short exposure to aluminium causes a fast change in cell patterning instead of a general toxic effect. Similarly, effects of UV‐B radiation on cell division are complex, with some studies reporting reductions in numbers of epidermal cells (Hopkins, Bond & Tobin 2002), and others increase in parenchyma cells (Staxen & Bornman 1994). Again, these data suggest changes in patterning rather than a general toxic effect.…”
Section: Simr – a Cellular Viewmentioning
confidence: 99%
“…In other studies, UV‐B resulted in decreases of plant productivity, biomass and leaf area (Li, Yue & Wang 1998; Yuan et al 2000), increases in leaf thickness and specific leaf mass (Rozema et al 1997; Rozema et al 1999a) as well as changes in biomass allocation (Li et al 1998). UV‐B‐induced differences in leaf surface morphology include changes in the number and size of epidermal and stomatal cells (Stewart & Hoddinott 1993; Staxen & Bornman 1994; Visser et al 1997). Inhibition of photochemical efficiency, indicated by decreases in F v / F m , has been observed under UV‐B supplementation (Sprtova, Nedbal & Marek 2000), although – in general – photosystem II is not regarded a direct target of UV‐B, particularly under realistic elevation of UV‐B in the field (Nogues & Baker 1995; Allen, Nogues & Baker 1998).…”
Section: Introductionmentioning
confidence: 99%